The role of recovered thiols in venous endothel adaptation in case of autovenous reconstruction of lower limb arteries - R. E. Kalinin; Yu. V. Abalenikhina; A. S. Pshennikov; S. A. Vinogradov (Бюллетень сибирской медицины, 2021)
Purpose. To evaluate the role of thiol status and its correlative relationship with the level of nitric oxide metabolites and vascular endothelial growth factor A (VEGF-A) in the blood plasma of patients with critical lower limb ischemia (CLI) after autovenous reconstructions of femoropopliteal segment’s arteries in the setting of venous endothelium of the arterial bed.Materials and methods. 54 patients with critical lower limb ischemia had been examined and divided into groups: synthetic prosthesis, in situ autovenous bypass procedure and reversed vein autovenous bypass  procedure. Peripheral venous blood was taken on the 1st and 10th days, and in 1, 3 and 6 months after the operation. Nitric oxide metabolites level was examined with photocolorimetric method by reaction with Griess reagent on a microplate analyzer (Awareness Technology, USA). VEGF-A number estimation was done by ELISA test (PersonalLab, Italy) with the use of Human VEGF-A Platinum ELISA. The level of thiol (SH-) groups was estimated with the use of Ellman’s reagent (SERVA, Germany) on spectrophotometer (Saint-Petersburg, Russian Federation).Results. The concentration of VEGF-A and the level of SH-groups increase on the 10th day and after 1 month in the group of patients operated on using a synthetic prosthesis. The level of NO metabolites, the concentration of VEGF-A, and the content of SH-groups increase statistically significantly and then decrease to the initial values in the group of patients operated on by reversed vein autovenous bypass procedure. In the group of patients operated on by the in situ method, the level of nitric oxide metabolites increases, the concentration of VEGF-A increases on the 10th day, the level of SH-groups increases, and a positive correlation was found between the content of SHgroups and the concentration of VEGF-A. Conclusion. NO metabolites contribute to the build-up of SH groups and VEGF-A in patients operated by the “reversed vein” method, and in patients in the in situ group, the concentration of VEGF-A and the level of  SH groups are not affected, which may be of clinical importance when prescribing NO donors. The revealed patterns of change in the level of recovered thiols, nitrogen oxide metabolites, VEGF-A in combination with analysis of early and late postoperative complications make it possible to conclude the advantage of  autovenous reconstruction of the femoropopliteal segment due to functional adaptation of the venous endothelium compared to the group of patients, operated on by the method of “synthetic prosthesis”. Method in situ on biochemical and angiological indicators proved to be more favorable in terms of the clinical course, than the “reversed vein” method.